Evaluación del consumo energético del plantel de RECOPE en la Garita, Alajuela - Vega-Méndez, Jessie Susana (Instituto Tecnológico de Costa Rica, 2012)
The evaluation of energy consumption RECOPE campus in Garita, Alajuela was the development of a diagnosis of electrical energy consumption of the main loads and campus areas, generating baseline information to guide decision-making in savings energy and identify energy saving options to help improve their environmental performance. Consequently, with national laws that guarantee the efficient use of energy as the Act Regulating the rational energy use No. 7447 and with the current global trend of promoting energy efficiency and alternative energy development, within the framework global warming and dependence on fossil fuels. The study identified a total energy consumption of 156 785 kWh for campus distribution, of which 71.43% corresponds to the use of electric motors used pipeline oil and sales, 16.83% for lighting, 9.58% for air conditioning and the remaining 2.16% consumption by office equipment and appliances. As major energy consuming areas were identified: the pipeline oil with a monthly consumption estimate of 107 075 kWh which represents 68% of the electricity that enters the campus and the freight yard with a consumption of 35 987 kWh per month which is 23% of the total consumption. The opportunities for energy conservation identified were oriented toward change by new technologies such as the replacement of outdoor luminaires for LED lighting or solar type and towards energy management as regards the establishment of criteria for selecting better engines electrical and air conditioners, the implementation of energy indices, improved power factor and the continued awareness of employees as major players in energy management on campus.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2012.
Keywords: Ahorro energético; Energías limpias; Conservación; Energía; Consumo energético